Outcomes of Using Heart Sound Simulator in Teaching Cardiac Auscultation - Akins, Ralitsa; Ho, Hoi (Canadian Medical Education Journal, 2010)
Background - Despite continued curriculum reform, the clinical skills competencies of medical graduates at all levels are steadily declining within a training system, where bedside opportunities become a luxury and the laboratory tests prevail over the clinical skills. While high-fidelity expensive simulators are being embraced by high-procedure volume specialties, low-fidelity and relatively inexpensive simulators, such as the heart sounds simulators remain under-utilized in medical training. Methods - We used a commercially available heart sound synthesizer in 2-hour training sessions with students and residents. Pre-post testing was completed at the beginning of the training session and three weeks after the session; participant responses were recorded by audience interactive response system. Results - Data analysis was accomplished with statistical software SPSS 17.0 utilizing paired t-test, and showed a statistically significant difference in learners’ knowledge and skills attainment 3 weeks after completion of the simulation training (p<0.0001). Conclusions - Based on our findings and the review of literature, we recommend that heart sound simulation is introduced at medical student level as the standard for teaching cardiologic auscultation findings and as preparation for auscultation of live patients. We also suggest that training with digitally simulated heart sounds is similarly beneficial in resident training.